Impact of switching to new spirometric reference equations on severity staging of airflow obstruction in COPD: a cross-sectional observational study in primary care - Sluga, Romina (Prim Care Respir J, 2014)
BACKGROUND: Severity of airflow obstruction in chronic obstructive pulmonary disease (COPD) is based on forced expiratory volume in one second expressed as percentage predicted (FEV(1)%predicted) derived from reference equations for spirometry results. AIMS: To establish how switching to new spirometric reference equations would affect severity staging of airflow obstruction in the Dutch primary care COPD patient population. METHODS: Spirometry tests of 3,370 adults aged ≥40 years with obstruction (postbronchodilator FEV(1)/forced vital capacity (FVC) <0.70) were analysed. The presence and severity of obstruction were defined using Global Initiative for Chronic Obstructive Lung Disease (GOLD) criteria. Postbronchodilator FEV(1)%predicted was calculated using three reference equations: corrected European Community of Steel and Coal (ECSC) (currently recommended in Dutch primary care), Swanney et al., and Global Lung Initiative (GLI). Discordances between severity classifications based on these equations were analysed. RESULTS: We studied 1,297 (38.5%) females and 2,073 males. Application of contemporary reference equations (i.e. Swanney and GLI) changed the GOLD severity stages obtained with the ECSC equations, mostly into milder stages. Severity of airflow obstruction was staged differently in 14.0% and 6.3%, respectively, when the Swanney et al. and GLI reference equations were applied. CONCLUSIONS: Compared with the (corrected) ECSC equations, switching to more contemporary reference equations would result in lower FEV(1) predicted values and affect interpretation of spirometry by reclassifying 6–14% of primary care COPD patients into different (mostly milder) severity stages. If and how this will affect GPs' treatment choices in individual patients with COPD requires further investigation.